Benign sinonasal tumours: From diagnosis to treatment - Gomes, Patrícia S. (2019)
Aim: Clinical, imaging and therapeutic characterization of Benign Sinonasal Tumours (BST).Study Design: Retrospective studyMaterial and Methods: Review of clinical files of BST patients undergoing endoscopic sinonasal surgery (ESS) between 2011 and 2017.Results: 32 patients with a mean age of 55.0±17.5 years were included. The most frequent BST were sinonasal papillomas (SP) (43.8%), followed by osteomas(31.3%). Symptoms included nasalobstruction(87.5%), headache(37.3%), hyposmia(34.4%) and epistaxis(25.0%). There was excellent concordance between the histology of the biopsy and that of the surgical specimen(K=0.90).SP presented both superior bone remodeling and Lund-Mackay score than other BST(p<0.01). ESS was associated with an external approach in 5 patients. Recurrence was observed in four SP and one hamartoma.Conclusions: BST are uncommon and present significant morbidity if not diagnosed in a timely manner. Despite the increasing importance of ESS, the associated or isolated use of external approaches is essential, in selected cases, for complete tumour resection.